In vitro starch digestibility and glycemic response of formulated barnyard millet bread (Journal of Food and Dietetics Research, 2025)
Barnyard millet is a grain crop of drought resistant and it is generally grown as a rainfed crop and consumed just like rice with potential benefits to human health. Its digestibility of protein is 40 per cent. However, processed barnyard millets digestion properties have not been reported. So in this study, the in vitro starch digestibility and in vivo glycemic indices (GI) of raw, boiled, roasted and germinated barnyard millet incorporated bread products were investigated at the percentage of 10,20,30,40, and 50 replacing the wheat flour. The results showed that the kinetic constant, k, which reflects the rate of hydrolysis in the early stage, ranged between 0.0295 and 0.1559. The k was the lowest in roasted barnyard millet bread, and high in raw barnyard millet bread.  More interestingly, the trend of C∞ and k were not fully consistent with each other. The highest incorporation of the barnyard millet flour (50%) incorporated bread showed the lower eGI. Among various processing technique, all variations of germinated barnyard millet breads showed low eGI followed by raw barnyard millet breads. Medium eGI was observed in all variations of both boiled and roasted barnyard millet breads. Therefore, barnyard millet, especially the processed millet, may serve as a potential source of nutraceutical and functional food that could delay the development of type 2 diabetes.
Keywords: Barnyard millet; Bread; Starch digestibility; Glycemic Index